2016
DOI: 10.11591/ijece.v6i5.10973
|View full text |Cite
|
Sign up to set email alerts
|

Bangladesh Perspective: Vehicle Speed Proposition System using Localized Wireless Identification

Abstract: Even in the era of advanced engineering, road accident has been a regular phenomenon causing death of many people in Bangladesh due to over speeding action of reckless drivers. There are several key places (such as schools, colleges, hospitals, highways and constructional areas etc.) where the speed of the vehicle should be lessened to avoid accidents. The roads and highways authority may place the speed limiter signboards in these areas to avoid these accidents, but these are frequently overlooked by the driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…There are several studies of the HC-12 modules for various purposes, as shown in Table 1. Analyse the phase delay of a propagating wave between two receiver antennas [17] Safety and security of coal mine workers Analyse different parameters and take actions to mitigate all hazards [18] Collision detection robot car model Analyse collision avoidance and maintain a safe distance between cars [19] Vehicle platooning prototype car model Analyse predictive controller and navigation algorithms in longitudinal and path control [20] Vehicle to vehicle communication Analyse to attenuate vehicle noise to some degree and reduce vehicle horn [21] Traffic signal control system Analyse an efficient route with a traffic light for emergency vehicles [22] Vehicle speed proposition system Analyse to reduce accidents and warn drivers of the speed limit at high accident zones [23] Collision prevention and warning system Analyse to reduce collision and damage in circumstances of accidents [24] Motorcyclist intelligent helmet Analyse to decrease violation by riders of traffic rules and cause accidents [25] Smart motorcyclists protection system Analyse to reduce road accidents by riders under the influence of alcohol [26] Toll gate system Analyse to apply contactless transaction overcoming the queue. [27] Electric vehicle telemetry data system Analyse to monitor and acquire onboard telemetry data of the electric vehicle.…”
Section: Related Workmentioning
confidence: 99%
“…There are several studies of the HC-12 modules for various purposes, as shown in Table 1. Analyse the phase delay of a propagating wave between two receiver antennas [17] Safety and security of coal mine workers Analyse different parameters and take actions to mitigate all hazards [18] Collision detection robot car model Analyse collision avoidance and maintain a safe distance between cars [19] Vehicle platooning prototype car model Analyse predictive controller and navigation algorithms in longitudinal and path control [20] Vehicle to vehicle communication Analyse to attenuate vehicle noise to some degree and reduce vehicle horn [21] Traffic signal control system Analyse an efficient route with a traffic light for emergency vehicles [22] Vehicle speed proposition system Analyse to reduce accidents and warn drivers of the speed limit at high accident zones [23] Collision prevention and warning system Analyse to reduce collision and damage in circumstances of accidents [24] Motorcyclist intelligent helmet Analyse to decrease violation by riders of traffic rules and cause accidents [25] Smart motorcyclists protection system Analyse to reduce road accidents by riders under the influence of alcohol [26] Toll gate system Analyse to apply contactless transaction overcoming the queue. [27] Electric vehicle telemetry data system Analyse to monitor and acquire onboard telemetry data of the electric vehicle.…”
Section: Related Workmentioning
confidence: 99%